Efektivitas Pembelajaran Daring Berbasis WhatsApp Group Berbantuan LKPD Ditinjau dari Motivasi Siswa - Kina Atma Rani; Tri Astuti Arigiyati; Irham Taufiq (Universitas Sarjanawiyata Tamansiswa, 2021)
This research is a quasi experimental research which aims to determine whether online learning based on WhatsApp Group with LKPD assistance is more effective than online learning based on WhatsApp Group without assistance from LKPD in terms of student learning motivation towards mathematics learning outcomes of seventh grade students of SMP Negeri 2 Jetis. The subjects of this study were students of class VII SMP Negeri 2 Jetis. Data collection techniques used documentation techniques, test techniques, and mathematics learning motivation questionnaire. The results showed that online learning based on WhatsApp Group with the assistance of LKPD was as effective as online learning based on WhatsApp Group without the assistance of LKPD and the learning outcomes of students with high and moderate motivation were better than the learning outcomes of students with low motivation